HOTSPOT TEST EVALUATION USING THERMOVISI FLIR ON 60 MVA TRANSFORMER CONDUCTOR BAY III - Fahturozi, Rela; Mubarok, Rizky; Munawar, Aris; Fachruroji (Program Studi Teknik Elektro Universitas Peradaban, 2024)
The operation of the transformer power distribution is the center of the transmission and distribution system. Given the almost continuous hard work of the transformer, its operation needs to be considered to prevent several disturbances that can reduce the optimal work of the transformer. One of the disturbances that can be found in the substation transformer is the hot-spot temperature at the terminal connection between the conductor cable and the equipment at the substation. This temperature is closely related to the protection and reliability of the system in the switchyard. To overcome the problems that occur in the transformer, especially the 150 kV Kalibakal Purwokerto Substation regarding the hot spots that occur at the transformer conductor bay connection. Routine temperature checks are carried out every day at the transformer connection point using a Thermovisi Flir E60 thermal imager measuring instrument that can determine the temperature value at the conductor connection clamp by looking at the infrared light from the tool. The results of the test evaluation carried out in this thermovisi method use the calculation of the temperature difference (∆T) between the clamp and the conductor, the results obtained are that none of the temperatures exceed >10˚C. The calculation of the emissivity value using Stefan Boltzman's law obtained an average emissivity of 0.506, which means it is included in the temperature range in accordance with the Standard Reference Material (SRM) (aluminum emissivity 0.5). Precision testing with a precision percentage expressed by the Coefficient of Variation (CV) obtained from 45 test points is 0.23%, this result can be categorized as a good result from the CV value standard of <2%. The calculation of the accuracy test found a result of 99.88%, which means that the points tested are still in good condition.